Cross-Ethnic Self-Disclosure Buffering Negative Impacts of Prejudice on International Students’ Psychological and Social Well-Being - Imai, Tatsuya; Imai, Ayako (Journal of International Students, 2019)
Intergroup contact theory suggests that developing a close relationship with outgroup members ameliorates the negative impact of prejudice that individuals perceive from outgroup members. This article specifically investigates the moderating role of cross-ethnic self-disclosure in the link between international students’ perceived ethnic/racial prejudice and depression as well as loneliness. One hundred and forty-three international students in Japan were asked to rate their perceived prejudice, depression, and loneliness as well as their self-disclosure to host nationals. The results showed that self-disclosure buffers the negative effects of prejudice on depression and loneliness such that international students who were more likely to disclose themselves to host nationals were less likely to be influenced by prejudice. Theoretical and practical contributions are considered.